Evaluation of Policy Implementation of Regional Public Service Agencies (BLUD) Toward Patient Satisfaction Perspective at RSUD Landak (Universitas Negeri Semarang, 2018)
Application of financial management flexibility independently exist in BLUD policy as one alternative to overcome the problem by the central government-run hospitals to regional government to fulfill its resources that are expected to improve the efficiency, effectiveness and productivity kenerja finances and improving the quality of service performance. Financial performance and good service can determine the quality of service quality at the hospital so that patients feel satisfied with the services received, the study aims to evaluate policy implementation BLUD at RSUD Landak using the CIPP model of evaluation. This study is a qualitative evaluation approach desktiftif. Sources of data in this research with in-depth interview data collection techniques as the primary data and secondary data obtained documents and observation techniques. Context evaluation found RSUD Landak mission and vision is not fully achieved, however BLUD policies have a positive impact on the achievement of the vision and mission RSUD Landak. The input evaluation found that the implementation of MSS and the fulfillment of the organizational structure in RSUD Landak had not reached the target of MSS and the organizational structure had not been fulfilled in terms of human resources, but the BLUD policy has a positive impact on improving MMS performance and efforts to meet HR in services and other functional at the RSUD Landak. Process evaluation found factors that hindered the implementation of BLUD policy in RSUD Landak. Product evaluation was found based on 14 indicators of HPI categorized as good for all HPI indicators in RSUD Landak.